(untitled) (Advances in Systems Science and Applications, 2017)
This paper aims to analyze the impediments to the development of entrepreneurship in Russia from the institutional perspective. To describe the institutional environment we use a concept of a three-dimensional institutional profile which classifies the institutions into three types: regulatory, cognitive and normative. These three dimensions imply three bases of legitimacy: entrepreneurship can be legitimized if it conforms to legal requirements (regulatory dimension), if it is seen as legitimate through a common frame of reference (cognitive dimension) and if it conforms to the existent moral base (normative dimension). We argue that one of the impediments to entrepreneurship development in Russia is that it is not seen as legitimate enough by the society at large. We explore the foundations for this through the regulatory dimension (the dynamic of the legal legitimation of entrepreneurial activity from the Soviet epoch to the present times), in the cognitive dimension (the stereotype of entrepreneur and its origins), and in the normative dimension (basic assumptions which relate to the fundamental moral dimensions of entrepreneurial activity: assumptions about money, wealth, and work).